Utilization of the Use of Google Forms as an Online Quiz to Increase Vocabulary in Arabic Language Learning - Aisyah, Devy; Mudinillah, Adam; Rezi, Melisa; Hanifaturrahmi, Hanifaturrahmi (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2024)
In the current era of the Industrial Revolution 5.0, it is time for internet access to be very important and influential in everyday life. Because in everyday life, knowledge is needed about how to use the internet well, the answer can be taken from one example: using Google Forms in the learning process. To better understand the use of Google Forms, research was conducted, and this study aims to explain the use of Google Forms as online quizzes to increase vocabulary in Arabic learning in universities. This research method is quantitative, where researchers distribute questionnaires or questionnaires focusing on students majoring in Arabic Language Education to make it easier for researchers to get more accurate data. The results of this study show that Google Forms can be used as an Online Quiz to improve vocabulary in Arabic language learning. With the results of research taken from survey data, the researchers concluded that Google Form is beneficial to be used as an Online Quiz in Arabic learning and the need to add features to Google Form to improve 4 Arabic language skills, especially in speaking skills. The limitation of this study is that researchers can only explain the benefits of using Google Forms as Online Quizzes in general. In line with that, it is expected that further researchers will be able to conduct research by explaining in detail the use of Google Forms as Online Quizzes in Arabic language learning.